PENGARUH PRAKTIK TRANSFER PRICING PERUSAHAAN MULTINASIONAL TERHADAP PENERIMAAN PAJAK DI NEGARA BERKEMBANG : STUDI KASUS DI INDONESIA - Parlindungan (Yayasan Pendidikan Literasi Borneo, 2025)
Transfer pricing practices conducted by multinational companies pose major challenges for developing countries, including Indonesia, in optimizing tax revenues. This article aims to analyze the impact of transfer pricing practices on tax revenues in Indonesia by reviewing regulations, implementation, and case studies in strategic sectors. This research uses a qualitative approach through literature review and secondary data analysis from official DJP reports, OECD, and academic publications. The results show that transfer pricing practices potentially reduce Indonesia's tax base by shifting profits to low-tax jurisdictions. Although the government has implemented transfer pricing documentation policies and Advance Pricing Agreements (APA), challenges remain in supervision, transparency, and human resource capacity. In conclusion, transfer pricing significantly affects tax revenues in Indonesia and requires stronger regulation and more effective international cooperation.